SISTEM NILAI TUKAR MATA UANG DAN PENERAPANNYA DI INDONESIA - Sulasmiyati, Sri (FIA UB, 2008)
Abstract In globalization era foreign money is one of the most important things in the human daily economic life. It is used not only for paying or buying something, but also for goods itself The government policy to regulate foreign exchange rate (kurs) system is also very important. The influential of this policy in one country’s economic condition and business transactions is very crucial too. Indonesia as one of a Small-Opened Economy Country needs an appropriate foreign exchange rate system to encourage economic condition’s growth. Since 1970s Indonesia had been implemented three exchange rate systems. That are: Fixed Exchange System (1970 — 1978), Managed Floating Exchange Rate System (1978 — July 1997) Freely Floating Exchange Rate System (since 14 A gust 1997). Keywords: Exchange rate system, Indonesia’s exchange rate systems